PERKEBUNAN KELAPA SAWIT DI LAHAN PASANG SURUT - Syaiful Hadi (Indonesian Journal of Agricultural Economics, 2016)
Limitations of potential land for oil palm led the development of oil palm plantation to tidal wetlands which is have various limiting factors hampered drainage, high salinity, the potential content of pyrite, peat depth dan maturity. The development of oil palm plantation to tidal wetland required investment cost dan operatinal cost are higher than mineral land or peat land. On the other hand, the production dan productivity of freshfruit bunch (FFB) is much lower with shorter economic life of the oil palm.